Relevansi Pemikiran Pendidikan KH M.A. Sahal Mahfudh Dengan Sistem Pendidikan Islam Kontemporer - Ahmad Mukhlis Anwar; Burhanuddin Ridlwan (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This study examines KH. M.A. Sahal Mahfudh's thoughts on Islamic education and its relevance in the context of contemporary education in Indonesia. Through a qualitative approach with a library research method, this study analyzes Kiai Sahal's works and related literature. The results show that Kiai Sahal's thought offers an integrative, transformative, and contextual Islamic education paradigm. He emphasizes the importance of integrating religious and general sciences, holistic character building through the concept of Basic Values Sholih Akrom (NDSA), and an educational approach that is adaptive to the times. Kiai Sahal's thinking has significant relevance to efforts to reform Islamic education in Indonesia, especially in developing an integrative curriculum and character building. The implementation of his thoughts can be seen in various contemporary Islamic education policies and practices. However, challenges such as resistance to change and limited resources still need to be overcome. This research contributes to the development of Islamic education discourse that is responsive to modern needs without losing the roots of tradition